Curriculum Management in Achieving School Scope Educational Goals - Nurhadi, Hafidin; Hadiansah, Hadiansah; Erihadiana, Mohamad; Syah, Muhibbin (Jurnal Isema : Islamic Educational Management, 2024)
The curriculum is one of the important tools that determine the success of achieving educational goals in schools. The achievement of educational goals implemented in the application of the right curriculum depends on good curriculum management. This study aims to describe and analyze the implementation of curriculum management at SMPIT Assyifa Boarding School Wanareja Subang in an effort to achieve institutional goals. This research uses a qualitative approach with the type of field research. The results of this study indicate that: 1) The Educational Objective of SMPIT Assyifa Boarding School Wanareja Subang is "Creating a Generation of Rabbani who are Pious, Smart and have Leader Character". 2) To achieve the educational goals set by the institution, the curriculum applied at SMPIT Assyifa Boarding School Wanareja Subang is the "Assyifa Curriculum" which is a combination of the MAPADI Curriculum, the National Curriculum and the Dormitory & JSIT Curriculum